Unravelling the complex meanings and origins of zisha teapots in the Ming and Qing dynasties - Gao, X (2023)
This thesis investigates the emergence and popularity of zisha teapot manufacturing in Yixing, Jiangsu Province, China. The unglazed teapots, made from zisha clay using a slabbuilding technique, have been appreciated by tea consumers since the Late Ming dynasty onwards. The study employs a multidisciplinary approach, including ethnographic research, archaeological science, historical analysis, the concept of chaîne opératoire, and experimental archaeology, to examine various data sources and gain a comprehensive understanding of the origins and development of zisha teapots. By analysing the chemical, mineralogical, and geological properties of zisha clay and evaluating its cultural significance, commonly held assumptions about the uniqueness of this raw material are challenged. By detailing changes in the zisha clay recipes at the key site of Shushan, this thesis also questions the prevailing views about the association between zisha ware’s porosity and the flavour of the tea brewed in these pots. The chronological changes of zisha teapot-making techniques are reconstructed, providing new insights into the technical development of the ware and resolving the debate on the “first zisha potter” story as recorded in historical records. By combining textual and archaeological sources, the changes in zisha pot usage and teapot users are identified. Users’ changing tastes and their appreciation of the art and craftsmanship of zisha teapot production are reassessed based on the new findings of this research. By considering zisha teapots through multiple subtopics and testing the combined findings against one another, this study provides a new and holistic synthesis of the origins of these important wares. It expands our knowledge of the technological choices made by potters, shedding light on the intricate connections between clay material properties, pottery-making techniques, tea consumption, and the appreciation of zisha teapots.